Congenital myasthenic syndrome type 23 caused by a missense homozygous c.205G>T (p.Asp69Tyr) in SLC25A1 gene in four Emirati patients from a single family - Aisha M. AlShamsi; Qudsia R. Shaukat; Mohammed H. AlKuwaiti (Journal of Biochemical and Clinical Genetics, 2021)
Background: Congenital myasthenic syndromes (CMSs) are a clinically and genetically heterogeneous group of disorders caused by mutations that lead to altered neuromuscular junction transmissions. Recently, the solute carrier family 25 member 1 (SLC25A1) gene was described to cause CMS type 23. This gene encodes a mitochondrial citrate carrier, associated mainly with a severe neurometabolic disease like combined D-2- and L-2-hydroxyglutaric aciduria (D/L-2-HGA). Case presentation: Here, we report four Emirati patients with a homozygous missense variant in SLC25A1 with a phenotype restricted to relatively mild CMS. We performed whole-exome sequencing (WES) in two relatives who presented with CMS to identify the underlying causative gene. Conclusion: The WES analysis revealed the presence of a homozygous c.205G>T (p.Asp69Tyr) [(c.226G>T (p.Asp76Tyr)] in the SLC25A1 gene; the same variant was identified in the other members in this family with the same phenotype. This suggests that c.205G>T (p.Asp69Tyr) [(c.226G>T p.(Asp76Tyr)] is associated with a relatively mild CMS phenotype and can be considered as a founder mutation in our region. [JBCGenetics 2021; 4(1.000): 56-63]